Pendekatan Hermeneutik Dalam Studi Hadits : (Teori A Double Movement Fazlur Rahman) - Dwi Setia Kurniawan (CV. Ulil Albab Corp, 2022)
This study aims to reveal Fazlur Rahman’s thoughts about hadith with his double movement theory. Now a days haditsh present ini a “stagnant” and poor application consequently, that’s why we need to reinterpretation of hadith understanding. Hermeneutic is a “supporting instrument” however it is perceived able to create interpretation by combining textually element and hadith contextually through this hermeneutic approach at once, since a text could only come together in a context.